Characterizing the effect of multiple Fc glycan attributes on the effector functions and FcγRIIIa receptor binding activity of an IgG1 antibody. (7th June 2016) - Pace, Danielle; Lewis, Nathaniel; Wu, Tina; Gillespie, Ron; Leiske, Dan; Velayudhan, Jyoti; Rohrbach, Amanda; Connell‐Crowley, Lisa
Abstract : N‐linked Fc glycosylation of IgG1 monoclonal antibody therapeutics can directly influence their mechanism of action by impacting IgG effector functions such as antibody‐dependent cell‐mediated cytotoxicity (ADCC) and complement‐dependent cytotoxicity (CDC). Therefore, identification and detailed characterization of Fc glycan critical quality attributes (CQAs) provides important information for process design and control. A two‐step approach was used to identify and characterize the Fc glycan CQAs for an IgG1 Mab with effector function. First, single factor experiments were performed to identify glycan critical quality attributes that influence ADCC and CDC activities. Next, a full‐factorial design of experiment (DOE) to characterize the possible interactions and relative effect of these three glycan species on ADCC, CDC, and FcγRIIIa binding was employed. Additionally, the DOE data were used to develop models to predict ADCC, CDC, and FcγRIIIa binding of a given configuration of the three glycan species for this IgG1 molecule. The results demonstrate that for ADCC, afuco mono/bi has the largest effect, followed by HM and β‐gal, while FcγRIIIa binding is affected by afuco mono/bi and β‐gal. CDC, in contrast, is affected by β‐gal only. This type of glycan characterization and modeling can provide valuable information for development, manufacturing support and process improvements for IgG products that require effector function for efficacy. © 2016 American Institute of Chemical Engineers Biotechnol. Prog ., 32:1181–1192, 2016